Analyzing and exploring internationalization opportunities in the kitchen furniture market in Northern Sweden - Kittilä, Elisa (Lapin ammattikorkeakoulu, 2016)
The main objective of this thesis is to analyze and explore market growth opportunities for the kitchen furniture company in Northern Sweden. The research seeks to identify the resources and capabilities which are valuable, rare and imperfectly inimitable and create a source of a sustainable competitive advantage for the Company. The research is based on a qualitative single case study. The theoretical framework was created by theories on resource-based view of a firm´s internationalization and international market analyses as well as by relevant articles, books and studies. Furthermore, the empirical data was collected through semi-structured interviews as well as the author’s own observations. The results of the analyses include evaluations of the external and internal environment of the Competitors, Customers and the Company. The suggestion for the market entry plan is formulated by exploring the most suitable opportunities generated. The results of the study indicate that the Company has genuine growth prospects in Northern Sweden by creating a successful development plan based on the Company´s management decisions. The Company´s resources, capabilities and management´s commitment to organization support the selected market entry mode by direct export from a single country to a single market. According to the thesis findings, the approaches that best suit the Company’s strengths and objectives relate to the standardization of the products, economies of scale to meet the target market requirements. Ecosystem services in seeking the sustainable use of products and services emerged as an interesting aspect for the Company´s future research. Opinnäytetyön päätavoitteena oli analysoida ja tutkia keittiökalusteyrityksen kasvumahdollisuuksia Pohjois-Ruotsissa.Tutkimus pyrki tunnistamaan niitä yrityksen resursseja ja valmiuksia jotka ovat arvokkaita ja harvinaisia ja joita kilpailijat eivät voi jäljitellä luoden kestävää kilpailuetua yritykselle. Tässä laadullisessa tutkimuksessa käytettiin selittävää yksittäisen ...